The Westray Chronicles: A Case Study in Corporate Crime - McCormick, Chris (Fernwood, 1999)
Was the Westray mining disaster a tragic accident or a corporate crime gone unpunished? In this book authors from backgrounds as diverse as engineering to public relations are brought together to create a holistic picture of what happened at Westray. From an analysis of the geology of the underlying coal seam to an assessment of the difficulties of pinning legal responsibility on the company, the government or any of the managers, this book constitutes one of the few case studies of corporate crime in Canada. The contributors offer the reader challenging new ways to think about workplace disasters and occupational injuries. Each contributor brings their special expertise to bear in a way that makes complicated issues transparent to the most general reader. At the same time, footnotes and references guide the reader who desires more extensive information. – Publisher's description
OCLC: 48811303
Keywords: 1900-1999; Charbon Mines et extraction Accidents Nouvelle-Écosse Stellarton Histoire 20e siècle; Coal mine accidents; Coal mine accidents Nova Scotia Stellarton History 20th century; History; Nova Scotia Plymouth (Pictou); Nova Scotia Stellarton; Tragédie minière de Westray; Plymouth; Pictou; N.-É.; 1992; Westray Mine Disaster; Plymouth; Pictou; N.S.; 1992